Corrigendum: Nα -acetyl-L-ornithine deacetylase from Escherichia coli and a ninhydrin-based assay to enable inhibitor identification - Kelley, Emma H.; Osipiuk, Jerzy; Korbas, Malgorzata; Endres, Michael; Bland, Alayna; Ehrman, Victoria; Joachimiak, Andrzej; Olsen, Kenneth W.; Becker, Daniel P. (Frontiers in Chemistry, 2024)
Graphical Abstract